Jacques Derrida : law as absolute hospitality - De Ville, Jacques (Routledge, 2011)
Jacques Derrida: Law as Absolute Hospitality presents a comprehensive account and understanding of Derrida's approach to law and justice. Through a detailed reading of Derrida's texts, Jacques de Ville contends that it is only by way of Derrida's deconstruction of the metaphysics of presence, and specifically in relation to the texts of Husserl, Levinas, Freud and Heidegger - that the reasoning behind his elusive works on law and justice can be grasped. Through detailed readings of texts such as To speculate -- on Freud, Adieu, Declarations of Independence, Before the Law, Cogito and the histo.
"A GlassHouse book"--Cover
Keywords: Derrida, Jacques.; Derrida, Jacques; Law -- Philosophy.; Law -- Interpretation and construction.; Deconstruction.; Deconstructivism (Architecture); Droit -- Interprétation.; Déconstruction.; Déconstructivisme (Architecture); Deconstructivist.; deconstruction (theory); LAW -- Essays.; LAW -- General Practice.; LAW -- Jurisprudence.; LAW -- Paralegals & Paralegalism.; LAW -- Practical Guides.; LAW -- Reference.; Deconstruction; Law -- Interpretation and construction; Law -- Philosophy; Rechtsphilosophie.; Rättsfilosofi.